Food supplementation reveals constraints and adaptability of egg quality in the magpie Pica pica. (1st December 2015) - Siitari, Heli; Alatalo, Rauno; Pihlaja, Marjo; Hämäläinen, Jenny; Blount, Jonathan; Groothuis, Ton; Hytönen, Vesa; Surai, Peter; Soulsbury, Carl
Differences in the deposition of limited maternal resources to eggs can reflect the optimal allocation to manipulate offspring phenotype, or constraints caused by maternal condition. We examined multiple maternal substances transferred to eggs in the magpie Pica pica to test the hypothesis that certain substances represent constraint and some optimal allocation. We did this by supplementary feeding magpies prior to egg-laying and then comparing the effect of food on maternal substances in conjunction with laying order relative to a control group. Certain substances such as carotenoids, immunoglobulins and avidin responded positively to food supplementation, whereas others, such as testosterone and total protein content of eggs, did not. Immunoglobulin allocation increased with laying order in fed but not in unfed groups. Our results suggest that patterns of optimal allocation and constraint in maternally-provisioned substances co-occur within clutches. Furthermore, constraint and optimal allocation may co-occur within the same substance i.e. immunoglobulins, highlighting the complexities of maternal resource allocation.